(untitled) (Journal of Civil Engineering Researchers, 2017)
Concrete-filled steel tubular (CFT) columns are being more widely used in the construction of high-rise buildings, bridges, subway platforms, and barriers. Their usage provides excellent static and earthquake-resistant properties, such as high strength, high ductility, high stiffness, and large energy-absorption capacity. CFT columns provide the benefits of both steel and concrete. This Paper present a review about the investigation done on behaviour of concrete filled steel tube columns by various researchers.